2019
DOI: 10.1002/ecs2.2811
|View full text |Cite
|
Sign up to set email alerts
|

Resource selection of mule deer in a shrub‐steppe ecosystem: influence of woodland distribution and animal behavior

Abstract: Ungulates inhabiting arid ecosystems are reliant on productive forb and shrub communities during summer months to meet nutritional demands for survival and reproduction. In the western United States, expansion of woodland vegetation into shrub-dominated communities and the potential loss of habitat are of concern with regard to animal populations reliant on robust sagebrush shrub and forb vegetation. We used mixed-effects logistic regression to model resource selection of female mule deer (Odocoileus hemionus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 77 publications
(112 reference statements)
3
15
0
Order By: Relevance
“…Generally, we found that during summer and pre-rifle period, males used areas with more open canopies at night and tended toward denser canopies during the day (~13-14% canopy cover on average). This is consistent with behavior during summer in previous studies on mule deer in arid climates (Hayes and Krausman 1993, Tull et al 2001, Ager et al 2003, Morano et al 2019, where deer are more active in foraging areas at night and select resting areas with moderate canopy cover during the day (other ungulates, Giotto et al 2013, Long et al 2014. During the rifle season, habitat use by males was not related to density of canopy, but males increased distance from motorized routes, suggesting that avoidance of human activity was a priority behavior, as is true during hunting season in other ungulates (white-tailed deer [Odocoileus virginianus], Kilgo et al 1998; roe deer [Capreolus capreolus], Bonnot et al 2013;and elk, Proffitt et al 2013, Paton et al 2017, Spitz et al 2019, Lamont et al 2020.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Generally, we found that during summer and pre-rifle period, males used areas with more open canopies at night and tended toward denser canopies during the day (~13-14% canopy cover on average). This is consistent with behavior during summer in previous studies on mule deer in arid climates (Hayes and Krausman 1993, Tull et al 2001, Ager et al 2003, Morano et al 2019, where deer are more active in foraging areas at night and select resting areas with moderate canopy cover during the day (other ungulates, Giotto et al 2013, Long et al 2014. During the rifle season, habitat use by males was not related to density of canopy, but males increased distance from motorized routes, suggesting that avoidance of human activity was a priority behavior, as is true during hunting season in other ungulates (white-tailed deer [Odocoileus virginianus], Kilgo et al 1998; roe deer [Capreolus capreolus], Bonnot et al 2013;and elk, Proffitt et al 2013, Paton et al 2017, Spitz et al 2019, Lamont et al 2020.…”
Section: Discussionsupporting
confidence: 91%
“…Our landscape configuration allowed animals to remain on a mix of public and private lands but in areas where motorized route density (<0.6 km/km 2 on average in our study area) mediated disturbance. Our finding that females used habitat that remained greener longer (i.e., locations with an average brown down of ordinal day 234-240) reinforces the importance of autumn nutrition (Tollefson et al 2010, Hurley et al 2014 and productive summer habitat (Morano et al 2019) for female ungulates (Cook et al 2004). Female use of productive habitat in summer and autumn also reinforces the need for females to replace lost calories from lactation (Oftedal 1985, Parker et al 2009.…”
Section: Discussionsupporting
confidence: 75%
“…Resource selection can also be behaviorally motivated, such that individuals make different decisions as they transition among discrete behavioral states (Cooper & Millspaugh, 2001). For example, we may not expect animals to select the same land cover characteristics while foraging as they would during periods of rest or reproduction (Marzluff et al, 2004; Morano et al, 2019), and resident adults may differ in their selection compared with dispersing juveniles (Elliot et al, 2014). Unfortunately, quantifying variation related to individual characteristics and experiences is difficult and often impossible to measure fully, requiring alternative approaches to incorporate such information into models (Patterson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed selection for each dominant cover type using a resource selection function (RSF), in which probability of use was defined as the proportional use of that cover‐type relative to its availability within the home range, resulting in a third‐order selection (Aebischer et al, 1993 ; Boyce et al, 2002 ; Johnson, 1980 ; McKee et al, 2015 ; Morano et al, 2019 ). Specifically, we used functions within the adehabitatHR package (Calenge, 2006 ) in R statistical software (version 4.0.2, R Core Team, 2020 ) to create 95% kernel home ranges, and functions within the raster package (Hijmans et al, 2020 ) to extract our covariate data (Karns et al, 2012 ; McKee et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%